2006
DOI: 10.1111/j.1462-2920.2006.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic richness of vibriophages isolated in a coastal environment

Abstract: The purpose of this study was to characterize Vibrio parahaemolyticus viruses (VpVs) isolated from different environments within and adjacent to the Strait of Georgia, and to examine the relative influences of distance and environment on host-range and genetic richness. Nearly all seawater enrichment cultures (29/31) generated isolates, implying that VpVs were widespread in the virioplankton, yet at low abundances (< 1 l(-1)). Viruses were not detected in sediments (n = 99). Fourteen of the 16 viruses characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 66 publications
(124 reference statements)
3
66
0
1
Order By: Relevance
“…Heureusement, les bactéries sont aussi victimes de prédateurs naturels puisque, comme tous les autres organismes vivants, elles peuvent être infectées par des virus. Ces virus de bactéries, les bactériophages ou phages, sont très spécifiques ; ils infectent en général une seule espèce de bactérie et même souvent seulement certaines souches de l'espèce [1,2]. Presque toutes les espèces bactériennes peuvent être infectées par de nombreux phages différents.…”
Section: L'activité Antibactérienne Des Phages : Un Regain D'intérêtunclassified
“…Heureusement, les bactéries sont aussi victimes de prédateurs naturels puisque, comme tous les autres organismes vivants, elles peuvent être infectées par des virus. Ces virus de bactéries, les bactériophages ou phages, sont très spécifiques ; ils infectent en général une seule espèce de bactérie et même souvent seulement certaines souches de l'espèce [1,2]. Presque toutes les espèces bactériennes peuvent être infectées par de nombreux phages différents.…”
Section: L'activité Antibactérienne Des Phages : Un Regain D'intérêtunclassified
“…As viral lysis may influence phytoplankton population dynamics, algal resistance to viral infection could potentially be an important parameter in the selective forces that contribute to structuring phytoplankton communities. Growing evidence that viral control of bacterial hosts selects for virus-resistant bacteria under controlled conditions in culture experiments (for example, Middelboe, 2000; Middelboe et al, 2001;Mizoguci et al, 2003), have suggested that viral activity contributes to the high clonal diversity often observed in aquatic systems (for example, Comeau et al, 2006;Holmfeldt et al, 2007;Stenholm et al, 2008). Resistance to viral infection has also been demonstrated in populations of cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the single-host enrichment protocol may select for phages with a narrow host range (22,64), and infection and lysis by low-virulence phages, which typically have a broad host range (22), may not be detected in plaque assays (10). However, some marine phages are known to infect different strains of the same species (12,51,64) or even different species (10)(11)(12). Hence, the specificity of phage-host interactions in marine waters needs to be better characterized and understood.…”
mentioning
confidence: 99%